Pelatihan Mindfulness Teaching untuk Meningkatkan Kesejahteraan Subjektif Guru Sekolah Inklusi - Ulin Nuha Rahmawati; Fuad Nashori; Ratna S. Rachmahana (Psympathic : Jurnal Ilmiah Psikologi, 2020)
This study aimed to examine the effectiveness of mindfulness teaching training in improving the subjective well-being of teachers in an inclusive school in Yogyakarta. This research used non-randomized pretest-posttest control group design. There were 22 respondents which divided into 11 respondents for treatment group and 11 respondents for control group. They were asked to complete a survey consists of the satisfaction with life scale (SWLS) and positive and negative scale (PANAS) before and after experiment. The results showed that there is a significant difference between the subjective well-being of inclusive school teachers group given mindfulness teaching training and that of the teachers in the teachers group without mindfulness teaching training. This finding indicates that mindfulness teaching training was effective to improve inclusive school teachers’ subjective well-being.